Similar sports participation as the general population in Dutch persons with haemophilia; results from a nationwide study. Issue 5 (19th June 2021) - Versloot, Olav; van Balen, Erna C.; Hassan, Shermarke; Schols, Saskia E.M.; Leebeek, Frank W.G.; Eikenboom, Jeroen; Coppens, Michiel; van Vulpen, Lize F.D.; Smit, Cees; Driessens, Mariëtte H.E.; van der Net, Janjaap; Gouw, Samantha C.; et al.
Abstract: Introduction: Although sports participation is advocated in people with haemophilia (PWH), detailed data concerning sports participation in Dutch PWH is lacking. Aim: to assess sports participation in Dutch PWH (6‐65 years) compared to the Dutch general population (GP). Methods: Data from a nationwide, cross‐sectional study in PWH were analysed. Sports participation (type, duration, frequency) was assessed by the Modifiable Activities Questionnaire (MAQ), limitations in activities using the (Paediatric) Haemophilia Activities List ((Ped)HAL). Sports in the two highest categories according to the National Hemophilia Foundation classification were considered high‐risk sports. Groups were compared using Chi‐square testing. Results: A total of 524 Adult PWH (median age: 45 (IQR: 30–55); 37% severe) and 126 paediatric PWH (median age: 11 (IQR: 8–14); 52% severe) were included. Sports participation was higher in adults (70%) than the GP (58%) and similar to the GP in children (PWH: 68%, GP: 72%). High‐risk sports participation decreased with age in PWH: from 65% (6‐12 years) to 17% (50‐65 years), which was also observed in the GP. Sports participation in children was independent of severity (non‐severe: 67% vs. severe: 65%; P  = 0.97), but not in adults (non‐severe: 75%, severe: 62%; P  < 0.01). Non‐severe PWH played more high‐risk sports than severe PWH: children at 65% vs. 48% ( P  = 0.05), adults at 25% vs. 15% ( P  = 0.07). Discussion: These results suggest that sports participation in PWH was comparable to the GP. Sports participation was dependent of haemophilia severity in adults. Children were more involved in high‐risk sports than adults. More studies on sports‐related injury‐risk are needed for adequate counselling.